Adding a back care package to the primary healthcare; a community-based cluster-randomized trial - Ali Ahmadzadeh Amiri; Stéphane Genevay; Amir Ahmadzadeh Amiri; Fatemeh Daneshvar; Jamshid Yazdani Charati; Mohammad Ghafouri; Navid Moghadam; Ramin Kordi (Brain and Spine, 2023)
Introduction: The clinical course of LBP is complex and chronicity is more frequent than once thought. Moreover, insufficient evidence was found in support of any specific approach at the level of the general population. Research question: This study aimed to evaluate the effectiveness of providing a back care package through the primary healthcare system in decreasing the rate of CLBP in the community. Material and methods: Clusters were primary healthcare units with the covered population as participants. The intervention package comprised both exercise and educational content in the form of booklets. Data regarding LBP were collected at baseline, 3 and 9-month follow-ups. The LBP prevalence and the incidence of CLBP in the intervention group compared to the control group were analyzed using logistic regression through GEE. Results: Eleven clusters were randomized including 3521 enrolled subjects. At 9 months, the intervention group showed a statistically significant decrease in both the prevalence and the incidence of CLBP, compared to the control group (OR ​= ​0.44; 95% CI ​= ​0.30–0.65; P ​< ​0.001 and OR ​= ​0.48; 95% CI ​= ​0.31–0.74; P ​< ​0.001, respectively). Discussion and conclusion: The population-based intervention was effective in reducing the LBP prevalence and CLBP incidence. Our results suggest that preventing CLBP through a primary healthcare package including exercise and educational content is achievable.